642 Washington Street, July 1972 - Wells, Pat (Tufts Archival Research Center, 2005)
Street-level view south-southeast of 642 Washington Street. Signage and awnings adorn the facade of the building, which faces northwest. 6 3/8 x 4 3/8 Photographs